Comparative Analysis of Transformed Continuous Assessment Scores of Private and Public Secondary Schools in Osun State - BABATIMEHIN, Temitope; ADEOYE, Peter; OGUNSANMI, Olawale Ayoola (Ilorin Journal of Education, 2024)
Non-uniformity of continuous assessment scores assigned by teachers or schools indicates that there is an intrinsic issue with its comparability standard. The study examined the transformed Continuous Assessment (CA) scores of Osun State Junior Secondary Schools (JSS) for better comparability of scores among private and public secondary schools. The study adopted the ex-post-facto research design. The study population was 33,552 which comprised all JSS Class III students during the 2010/2011 academic session in both private and public secondary schools in Osun State. The sample consisted of 1200 students selected using a multistage sampling technique. A proforma titled Continuous Assessment Scores Retrieval was used as an instrument to collect CA scores of the selected students in English Language and Mathematics. Data were analysed using percentages and Pearson’s Product moment correlation statistics. Results showed that the transformed continuous assessment scores of private and public schools were above the mean score =0 and SD = 1 in Mathematics (62.70%) and English Language (66.0%). The results also showed that there was a significant positive relationship between the transformed continuous assessment scores and raw continuous assessment scores obtained by students in Mathematics and English Language (r=1.00; p<0.05). Results further showed that there was a significant difference in the transformed continuous assessment scores of private and public schools in Mathematics (t=5.341; p<0.05) and English Language (t=4.395; p<0.05). The study therefore concluded that transformed continuous assessment scores of private and public secondary schools in Osun State would be comparable if appropriate transformation models were used.